PELAKSANAAN KEWAJIBAN ANAK TERHADAP ORANG TUA STUDI KASUS UNIT PELAKSANA TEKNIS PELAYANAN SOSIAL TRESNA WERDHA (PSTW) KHUSNUL KHOTIMAH PEKANBARU DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Charisa Yasmine; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Marriage raises legal relations with the child born, the Marriage Act in Article 46, paragraph 2 states: if a child has grown, he is obliged to maintain according to his ability, parents and family in straight line upwards, if they need his help.The problems that the author made the basis in the study is how the implementation of the obligations of children against parents according to Law Number 1 Year 1974 About Marriage, and what is the factor of children entrust parents in the Technical Implementation Unit Social Service Tresna Werdha Khusnul Khotimah Pekanbaru. The research method used is descriptive sociological juridical. Source of data used in this research that comes from primary and secondary data. Data analysis uses qualitative data analysis and draw conclusion with deductive method.The results of this study on the implementation of the obligations of children to parents in Technical Implementation Unit of Social Services Tresna Werdha Khusnul Khotimah Pekanbaru when referring to Law Number 1 Year 1974 About Marriage that regulates the obligation of children to parents still found many deficiencies in the implementation. Where there are still children who neglect their parents and entrust to the nursing home. And the reason the child entrusted the parents there are three because of financial factors, the health of parents, and the work of children in the work. The conclusion of Law No. 1 of 1974 concerning Marriage in Article 46 paragraph (2) is implicitly explained about the obligation of the child to provide for his or her parents: the word